1979
DOI: 10.1172/jci109607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neomycin Alone and in Combination with Cholestyramine on Serum Cholesterol and Fecal Steroids in Hypercholesterolemic Subjects

Abstract: A B S T R A C T Effects of neomycin were studied on serum cholesterol and fecal steroids in hypercholesterolemic patients during a short treatment period (4 wk) and a long treatment period (16 mo), using small (1.5 g/d) and large (up to 6 g/d) doses alone and in combination with cholestyramine. In the short-term low-dose study the decrease in serum cholesterol by 21% was associated with a proportionate increase in fecal cholesterol elimination as neutral sterols through impaired cholesterol absorption. Serum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
2

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 30 publications
(31 reference statements)
3
19
0
2
Order By: Relevance
“…3). Measurements of absorption of exogenous cholesterol in three patients confirmed the findings of Sedaghat et al 3 and Miettinen et al 4 In our view, therefore, the fundamental action of neomycin on cholesterol metabolism is to block cholesterol absorption. It should also be emphasized that the reduction in the absorption of cholesterol included not only the small amount in the diet but also the much larger amount excreted in the bile.…”
Section: Effects Of Neomycin On Cholesterol Metabolismsupporting
confidence: 87%
See 1 more Smart Citation
“…3). Measurements of absorption of exogenous cholesterol in three patients confirmed the findings of Sedaghat et al 3 and Miettinen et al 4 In our view, therefore, the fundamental action of neomycin on cholesterol metabolism is to block cholesterol absorption. It should also be emphasized that the reduction in the absorption of cholesterol included not only the small amount in the diet but also the much larger amount excreted in the bile.…”
Section: Effects Of Neomycin On Cholesterol Metabolismsupporting
confidence: 87%
“…Some of the increment in fecal steroids may reflect a mobilization of cholesterol from tissue pools, 3 but for reasons discussed previously, 4 the magnitude and duration of the increase indicate that most of it was the result of heightened cholesterol synthesis. In most patients given neomycin, however, absorption is blocked to a such degree that losses cannot be replaced exactly by new synthesis.…”
Section: Effects Of Neomycin On Cholesterol Metabolismmentioning
confidence: 98%
“…Previous studies showed that under these experimental conditions, a reasonably steady state of sterol metabolism was obtained both with and without cholestyramine. 24 Thus, body weight was stable, plasma lipid values leveled off, and in successive fecal samples fecal steroids showed no constant increase or decrease. In growing children the sterol balance value (i.e., the difference between dietary cholesterol and fecal elimination of cholesterol as neutral sterols and bile acids) may underestimate cholesterol synthesis because growing tissues retain some cholesterol.…”
Section: Family Studiesmentioning
confidence: 94%
“…Bile acid sequestrants such as cholestyramine bind bile acids in the intestinal lumen, thereby preventing their reabsorption. Loss of bile acids from the enterohepatic circulation results in derepression of 7a-hydroxylase expression (6)(7)(8)(9)(10) and an increase in the rate of bile acid synthesis (9,11). The liver compensates for the accelerated loss of cholesterol by increasing the rate of de novo cholesterol synthesis and, if this is inadequate, by increasing the receptordependent uptake of LDL from plasma (10), thereby lowering circulating LDL levels.…”
Section: Introductionmentioning
confidence: 99%